Association between Hemoglobin Glycation Index and In-Hospital all-cause mortality of patients with Congestive Heart Failure: a retrospective study utilizing the MIMIC-IV database - Sun, Ling; Yuan, Jie; Wang, Tao; Ning, Bin; Yuan, Qinghua (Frontiers in Endocrinology, 2025)
BackgroundThe aim of this study was to explore the relationship between the hemoglobin glycation index (HGI) of Congestive Heart Failure (CHF) patients and their risk of mortality within 365 days.Patients and methodsThe Medical Information Mart for Intensive Care (MIMIC-IV) database supplied the patient data for this study, which was categorized into quartiles based on the HGI. The primary endpoint was all-cause mortality within a 365-day period. Kaplan-Meier (K-M) analysis was utilized to compare this primary endpoint across the four aforementioned groups. The relationship between the HGI and the endpoint was examined using restricted cubic splines (RCS) and a Cox proportional hazards analysis.ResultsA total of 985 patients were included in this study. HGI was significantly associated with 30 days mortality (15.9%; HR, 0.79; 95% CI, (0.67~0.92); P=0.003) and 60 days mortality (19.3%; HR, 0.83; 95% CI, (0.72~0.96); P=0.011) and 90 days mortality (22.1%; HR, 0.86; 95% CI, (0.75~0.99); P=0.031) and 365 days mortality (30.7%; HR, 0.97; 95% CI, (0.86~1.09); P=0.611) in patients with critical CHF in the completely adjusted Cox proportional risk model. RCS analysis revealed a U-shaped relationship between HGI and outcome events. KM curves survival analysis suggests a correlation between 30 days and 365 days mortality in HGI and CHF patients.ConclusionsA higher HGI has a more protective effect than a low HGI for patients with CHF and was directly associated with short-term mortality rates. These findings may be helpful in the management of patients with CHF.